2002
DOI: 10.1524/ract.2002.90.6.337
|View full text |Cite
|
Sign up to set email alerts
|

Ion-molecule reactions of Ru+ and Os+ with oxygen in a Penning trap

Abstract: Chemistry of superheavy elements / Ru + , Os + , Ti + , Zr + / Ion-molecule reactions / Penning trap Summary. Gas-phase ion chemistry in a Penning trap has been explored for future experiments on the chemical properties of the heaviest elements. The Mainz Cluster Trap, a Penning trap experiment devoted to metal cluster research, has served as a model apparatus for SHIPTRAP which is being installed behind the velocity filter SHIP (Separator for Heavy Ion reaction Products) at the Gesellschaft für Schwerionenfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 136 ) The EA measurements of the heaviest elements are of potential interest. A new stage of chemical investigations of the heaviest elements using their ion beams, such as gas-phase ion chemistry 137 141 ) and ion mobility measurements, 119 , 142 ) will open new avenues to the heaviest element chemistry.…”
Section: Discussionmentioning
confidence: 99%
“… 136 ) The EA measurements of the heaviest elements are of potential interest. A new stage of chemical investigations of the heaviest elements using their ion beams, such as gas-phase ion chemistry 137 141 ) and ion mobility measurements, 119 , 142 ) will open new avenues to the heaviest element chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[52] For both cases, the stabilization of defined chemical species and the kinetic effects during their formation and transport are the most challenging tasks to be addressed. For instance, in preparatory experiments for group 7 and group 8 transactinides, Bh [53] and Hs, [54] it was observed that the oxidation of these elements to high oxidation states in oxygen and water-containing reactive gases is, despite being thermodynamically favored, severely kinetically hindered, i.e. an observation possibly interesting for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This novel technique studies the chemical properties of these elements in the gas phase utilizing the combined capabilities of the Berkeley gas-filled separator (BGS) and the recently installed FIONA (For the Identification of Nuclide A ) mass analyzer. This setup allows (i) the production of ions of heavy and super heavy elements, (ii) separation of those ions from the beam and unwanted nuclear reaction products in the BGS, (iii) the ability to trap and cool the ions in an ion-trap in FIONA, where (iv) reactive gas can be introduced and allowed to react with the trapped ions for a fixed interval of time, and (v) the number and mass of unreacted and reacted ions ejected from the trap can be directly measured. The new method is based on the studies with Penning traps, inductively coupled plasma selected-ion flow tube, and Fourier transform ion cyclotron resonance mass spectrometry . Experimental studies using this technique can provide quantitative information such as ionization potentials, bond-dissociation energies, and kinematic reaction rates.…”
Section: Introductionmentioning
confidence: 99%